2020
DOI: 10.1017/s1474746420000548
|View full text |Cite
|
Sign up to set email alerts
|

Into the Promised Land: Modelling the Role of Take-Up Agents in Realising Welfare Rights

Abstract: Throughout the years, social policy scholars have advanced a multi-level perspective of non-take-up, viewing it as is a complex process shaped by a broad range of interacting barriers and actors. However, a comparatively small amount of that scholarship has addressed the key role of take-up agents: professionals or semi-professionals who actively help clients realise their welfare rights. Moreover, most of this scant literature has tended to focus on the agents’ impact rather than on their role and practices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Van Oorschot (2001), for instance, has noted the importance of looking at issues of non‐take‐up at different levels (i.e., scheme level, administrative‐level and client level). Others also showed that different actors —such as volunteers, public sector agents and market agents— are able to use not only knowledge but also networking, emotions and power to address non‐take‐up (Holler & Benish, 2022).…”
Section: Brokers and The Migration‐welfare Nexusmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Oorschot (2001), for instance, has noted the importance of looking at issues of non‐take‐up at different levels (i.e., scheme level, administrative‐level and client level). Others also showed that different actors —such as volunteers, public sector agents and market agents— are able to use not only knowledge but also networking, emotions and power to address non‐take‐up (Holler & Benish, 2022).…”
Section: Brokers and The Migration‐welfare Nexusmentioning
confidence: 99%
“…For this reason, we do not include personal networks as such in our analysis. Second, building on the work of Holler and Benish (2022), our subsequent discussion of the practice of welfare brokerage highlights the need to also look at other resources beyond knowledge, such as power or emotions that brokers can leverage to conduct their missions.…”
Section: Welfare Brokers and Eu Mobility: Insights From The Experienc...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the literature indicates that personal counselling by take‐up agents, such as social workers, is a very effective means of helping people exercise their rights, especially when it comes to populations who have significant difficulty exercising their rights (Bateman, 2006). Take‐up agents provide important knowledge and help individuals get past emotional barriers preventing take‐up (Holler & Benish, 2022).…”
Section: Agency Social and Structural Characteristics And Access To K...mentioning
confidence: 99%
“…The underlying assumption is that formal and informal practices shape our encounters with state programs and their costs. Many such encounters are burdensome, leading also to various material, adversary consequences, as in the form of non-take-up of welfare rights (Finn and Goodship, 2014;Heinrich, 2016), or in outsourcing some of the claiming process to other take-up agents (Holler and Benish, 2022).…”
Section: Administrative Burdenmentioning
confidence: 99%